The Treaty of Waitangi and the Sealord deal - Munro, Justine (Victoria University of Wellington Law Review, 1994)
On 23 September 1992, the Crown and Maori representatives signed a deed in full and final settlement of Maori claims to fishing rights under the Treaty of Waitangi. This article asks whether the "Sealord deal", as it has come to be called, is in accordance with the principles of the Treaty of Waitangi, as these have been developed by the courts and the Waitangi Tribunal; and concludes that the deal represents only a pragmatic response to Maori needs and the opportunities at hand. The Sealord deal failed to confront the issues that must be addressed if legitimate and lasting Treaty claims settlements are to be made in New Zealand. This article incorporates events up to 1 September 1993. Key developments since that time and up to June 1994 are briefly summarised in the appendix.